COLLEGE BUILDING THROUGH WITH STANDARD CERTIFICATION ISO 9001: IMPLICATIONS AND IMPACT - Gutiérrez Huby de Segura, Ana María (2014)
The objective of this paper is to extend the application range of ISO 9001:2008 in Education Institutions related to the quality accreditation processes. To this purpose, performance implications using this regulation are presented. Furthermore, it will be ob-served to which extent the implementation of quality assurance processes are favorable to leading towards accreditation. Conclusions: The standardization of a quality manage-ment system based on ISO 9001 does not imply that education services offered have to be identical in the world. Normalization respects particular organization designs regarding the requirements they want to achie-ve, the documentation of how things are attained and the verification of accomplishments. Certification of the educational process quality will succeed if there have previously existed an education plan and a system of quality management, coordinated by a system of educational management where quality culture is the core idea of action.